Optimizing mathematics learning through Liveworksheet-based PBL: A classroom action research in Grade VII - Laily Amelia Hidayah (Jurnal Pendidikan Profesi Guru, 2024)
This classroom action research was conducted to address the low mathematical problem-solving skills observed among students at SMPN 16 Malang. The study aimed to enhance these skills by implementing a Problem-Based Learning (PBL) model integrated with interactive e-worksheets via the Liveworksheet platform. The participants were 32 seventh-grade students (Class VIIF). Data were collected through classroom observations and learning outcome tests, then analyzed using descriptive statistics. The results demonstrated a significant improvement in both student and teacher activity across two learning cycles. Student participation in PBL activities increased by 25%, while teacher activity improved by 13%. By the second cycle, 28 out of 32 students (90%) reached the success criteria, surpassing the targeted 80%. Additionally, the proportion of students in the high and very high performance categories increased by 22% and 23%, respectively, culminating in an overall achievement rate of 84%. The effectiveness of the interactive e-LKPD was rated as good in the first cycle (79%) and very good in the second cycle (90%). These findings suggest that integrating interactive e-modules in a PBL framework can effectively support mathematics instruction and contribute to the professional development of teachers through the application of innovative, student-centered learning strategies.